Strain- and Dose-Dependent Reduction of Toxoplasma gondii Burden in Pigs Is Associated with Interferon-Gamma Production by CD8+ Lymphocytes in a Heterologous Challenge Model - Jennes, Malgorzata; De Craeye, Stéphane; Devriendt, Bert; Dierick, Katelijne; Dorny, Pierre; Cox, Eric (Frontiers in Cellular and Infection Microbiology, 2017)
Toxoplasma gondii is a worldwide prevalent parasite of humans and animals. The global infection burden exceeds yearly one million disability-adjusted life years (DALY’s) in infected individuals. Therefore, effective preventive measures should be taken to decrease the risk of infection in humans. Although human toxoplasmosis is predominantly foodborne by ingestion of tissue cysts in meat from domestic animals such as pigs, the incidence risk is difficult to estimate due to the lack of screening of animals for infection and insights in location and persistence of the parasite in the tissues. Hence, experimental infections in pigs can provide more information on the risk for zoonosis based on the parasite burden in meat products intended for human consumption and on the immune responses induced by infection. In the present study, homo- and heterologous infection experiments with two distinct T. gondii strains (IPB-LR and IPB-Gangji) were performed. The humoral and cellular immune responses, the presence of viable parasites and the parasite load in edible meat samples were evaluated. In homologous infection experiments the parasite persistence was clearly strain-dependent and inversely correlated with the infection dose. The results strongly indicate a change in the amount of parasite DNA and viable cysts in porcine tissues over time. Heterologous challenge infections demonstrated that IPB-G strain could considerably reduce the parasite burden in the subsequent IPB-LR infection. A strong, however, not protective humoral response was observed against GRA7 and TLA antigens upon inoculation with both strains. The in vitro IFN-γ production by TLA-stimulated PBMCs was correlated with the infection dose and predominantly brought about by CD3+CD4-CD8αbright T-lymphocytes. The described adaptive cellular and humoral immune responses in pigs are in line with the induced or natural infections in mice and humans. Previous studies underscored the heterogeneity of T. gondii strains and the corresponding virulence factors. These findings suggest the potential of the IPB-G strain to elicit a partially protective immune response and to reduce the parasite burden upon challenge infection. The IPB-G strain could be used as a promising tool in limiting the number of viable parasites in edible tissues and, hence, in lowering the risk for human toxoplasmosis.